Bond characteristics of near-surface-mounted anchorage for prestressing. (1st September 2017) - Lee, Heeyoung; Lee, Woosung; Jung, Woo Tai; Chung, Wonseok
Highlights: A new grouted anchorage system is applied to the NSM strengthening technique. The bond behavior of anchorage for the post-tension method was investigated. 40 pullout tests with different fillers and diameters of the anchorage were conducted. Behavior and failure characteristics of tested anchorage systems were examined. The optimum mortar filler strength and sleeve diameters were proposed. Abstract: The external bonds of carbon fiber reinforced polymers (CFRP) used to strengthen structures are known to be vulnerable to delamination. To prevent FRP delamination and efficiently strengthen structures, post-tension CFRP rods are installed for near-surface-mounted (NSM) strengthening. For post-tensioning, grouted anchorage systems have been applied to the NSM strengthening technique. The bond behavior between the CFRP rods and the filler in the anchorage for the post-tension rods should be investigated. This study evaluates the behavior and failure characteristics of bond-type anchorage systems based on the results of 40 pullout tests with different mortar fillers and diameters of the anchorage sleeve. The optimum mortar filler strength and sleeve diameters have been proposed to ensure proper bond behavior in NSM anchorage systems.